Cultural Promotion Through Digital Media: Showcasing Sasak Women - Sumadewa, I Nyoman Yoga; Artayasa, I Nyoman; Remawa, Anak Agung Gede Rai; Swandi, I Wayan (MultiTech Publisher, 2024)
The role of women in the Sasak Tribe, apart from being a housewife, also has an important role in their social life. The role of Sasak women starts from childhood, becoming a skilled girl. This is a provision, because Sasak women are required to not only be good at taking care of the household and family, but also contribute to the family economy. Packaging Sasak women in the form of digital works so that the values contained are easy to accept among the current generation with an approach to the community or research target is carried out in various ways. The digital character is designed with full of values, in which it also includes forms of local wisdom from the point of view of life and local cultural wisdom in the form of daily habits and behavior in social interactions. The creation of this work uses the design thinking method of empathize, define, ideate, prototype, and test that is a process of realization of the phenomena that occur in society today, especially Sasak women, aesthetic elements that appear in this work such as the use of several accessories that add aesthetics and must be worn by Sasak women when attending events.